Contribution of NtZIP1-Like to the Regulation of Zn Homeostasis - Papierniak, Anna; Kozak, Katarzyna; Kendziorek, Maria; Barabasz, Anna; Palusińska, Małgorzata; Tiuryn, Jerzy; Paterczyk, Bohdan; Williams, Lorraine E.; Antosiewicz, Danuta M. (Frontiers in Plant Science, 2018)
Tobacco has frequently been suggested as a candidate plant species for use in phytoremediation of metal contaminated soil but knowledge on the regulation of its metal-homeostasis is still in the infancy. To identify new tobacco metal transport genes that are involved in Zn homeostasis a bioinformatics study using the tobacco genome information together with expression analysis was performed. Ten new tobacco metal transport genes from the ZIP, NRAMP, MTP and MRP/ABCC families were identified with expression levels in leaves that were modified by exposure to Zn excess. Following exposure to high Zn there was upregulation of NtZIP11-like, NtNRAMP3, three isoforms of NtMTP2 , three MRP/ABCC genes (NtMRP5-like, NtMRP10-like, and NtMRP14 like) and downregulation of NtZIP1-like and NtZIP4. This suggests their involvement in several processes governing the response to Zn-related stress and in the efficiency of Zn accumulation (uptake, sequestration and redistribution). Further detailed analysis of NtZIP1-like provided evidence that it is localized at the plasma membrane and is involved in Zn but not Fe and Cd transport. NtZIP1-like is expressed in the roots and shoots, and is regulated developmentally and in a tissue-specific manner. It is highly upregulated by Zn deficiency in the leaves and the root basal region but not in the root apical zone (region of maturation and absorption containing root hairs). Thus NtZIP1-is unlikely to be responsible for Zn uptake by the root apical region but rather in the uptake by root cells within the already mature basal zone. It is downregulated by Zn excess suggesting it is involved in a mechanism to protect the root and leaf cells from accumulating excess Zn.